CpG-free plasmid DNA exhibits limited in vitro reporter gene expression due to transcriptional incongruity - Habib Rahuman, Muhammad Omar (2017)
The use of efficient vector is essential in gene therapy, which has the promising potential to treat not only genetic diseases but also acquired diseases. Although plasmid DNAs (pDNA) have been shown to be a much safer alternative compared to viral vectors, limitations, like detrimental inflammatory response and transient transgene expression, hinder its clinical application. This is mainly due to the presence of unmethylated cytosine guanine (CpG) motifs on pDNA. As a solution, CpG-free pDNA (p0CpG) was developed, where CpG motifs are completely depleted from the pDNA backbone and transgene. In addition, the safety and efficacy of the p0CpG were further reinforced with significant therapeutic effect observed in a cystic fibrosis clinical trial. Given these points, extending the application of clinically relevant p0CpG towards ex vivo gene therapy would be a novel approach to treat many disorders. However, it was recently reported that the depletion of CpG motifs from transgene could affect the in vitro gene expression negatively. Similar results may also extend to p0CpG, as the p0CpG is also devoid of CpG motifs. Thus, the main objective of this study is to evaluate the performance of p0CpG in vitro, specifically the effect of CpG depletion from the transgene.